ANALISIS KOMPARATIF KINERJA PENGELOLAAN KEUANGAN DAERAH SEBELUM DAN SESUDAH PENGALIHAN PBB-P2 MENJADI PAJAK DAERAH DI KAB/KOTA SELURUH INDONESIA TAHUN 2012 - FARAH MAULIDA, ANANDA (Jurnal Akuntansi AKUNESA, 2015)
Local government’s financial performance analysis is one alternative that can be used to see the ability and success of local governments in implementing the regional autonomy. This research is quantitative research that has a purpose to knowing the comparison between financial performance of local governments districts and cities in Indonesia during the period before and after the transfer of PBB-P2 from central taxes to local taxes in 2012. The analytical tool that used to analyze the financial performance of local governments was using financial ratio analysis area, ratio of fiscal decentralization, ratio of the area of financial dependence, area of financial independence ratio, effectiveness ratio, efficiency ratio, activity ratio, and ratio of revenue growth. The results showed that on the ratio of fiscal decentralization and the ratio of revenue growth there are significant differences in the financial performance of local governments districts and cities during the period before and after of the transfer of PBB-P2 from central taxes to local taxes. But as long as, on the ratio of the area of financial dependence, ratio of financial independence ratio, effectiveness ratio, efficiency ratio and activity ratio there are no significant difference in the financial performance of local governments districts and cities during the period before and after of the transfer of PBB-P2 from central taxes to local taxes. Keywords : Performance of Local Governmets Finance, Diversion of PBB-P2, Local Governments Financial Ratios.